BUILDING A ROBUST SHARIAH GOVERNANCE POLICY: A QUALITATIVE STUDY ON SHARIAH BANKS IN BOGOR, INDONESIA - HARUN FAIZAL (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2021)
The purpose of this research is to explore the Shariah governance on customer trust in Islamic banking in Bogor, Indonesia. A mixed-method approach is utilized, combining a literature review and in-depth interviews with bank managers. The interviews provide insights into the strategies employed by banks to enhance Shariah governance and customer trust. Preliminary findings indicate a positive correlation between effective Shariah governance and customer trust. Customers value transparency, ethical practices, and the role of qualified Shariah scholars in governance. The study's implications emphasize the significance of strong governance mechanisms in fostering customer trust, which can enhance the competitive advantage of Islamic banks in Bogor's financial market.